The Dropout in Tertiary Education at Czech public and private universities as a result of school marketing. - Kučerová, Hana (My University, 2020)
The situation of tertiary education in the Czech Republic has changed dramatically in the last 15 years after joining the European Union. The demographic decline of the population, structural changes in the number of employees, the expansion of tertiary education and the impact of economic cycles change the overall extent and structure of the transition of university graduates to the labor market. The resulting changes can lead to serious problems, both on the supply side and the labor demand side. An equally significant impact on the dropout of university education has the implementation of school marketing. A school that makes better use of marketing in its activities has a greater chance of getting material and quality teachers. To some extent, private schools are in a better position because to have effective marketing policies in place for some time now. This article deals with the development of the dropout at public and private universities in the Czech Republic. Further, it compares the dropout according to the degree of the study program. The answers to the research questions were obtained through the analysis of secondary data (literature, research, annual reports and long-term intentions of universities. Based on the performed analysis, the fact that in the Czech Republic the dropout rate is increasing every year is confirmed and thus represents one of the main actual problems of the Czech public but also private universities.
Studijní neúspěšnost terciárního vzdělání na českých veřejných a soukromých vysokých školách jako důsledek školního marketingu.
Keywords: school marketing; public universities; private universities; dropout; education as a product; marketing škol; veřejné univerzity; soukromé univerzity; studijní neúspěšnost; vzdělání jako produkt